Evaluación de daños y residuos resultantes de las operaciones de aprovechamiento en seis concesiones forestales en la Región Ucayali, Amazonía Peruana - Colan, V.; Catpo, J.; Sabogal, C. (CIFOR and INRENA, 2007)
Harvesting operations in timber concessions have traditionally followed strategies related to enterprises' capacity in terms of available equipment and financing, industrial integration, commercialization of more species, physical accessibility to the concession, and quality of human resources, among others. Some more traditional forest enterprises interested in maximizing their production have began activities to monitor the performance of their personnel in each harvesting operation, and identify the environmental impact these cause in the residual forest. This is not a practice that can be generalized to the concessions operating in the Ucayali Region where most small to medium enterprises do not have enough knowledge about the utility of monitoring their operations. In this article we present information gathered in six timber concessions of theUcayali Region to assess the damage caused by their harvesting operations in the vegetation, soil and watercourses, as well as the harvesting residues. The impact in the vegetation resulted to be more intense with manual operations than with mechanized harvesting. The impact in the soil caused by mechanized operations was low in areas affected by gaps but highly variable in conditions such as roads and skid trails. Watercourses in general reflect poor planning of road infrastructure in the concessions. Harvesting residues were found without justification in logging gaps and along roads. It is concluded, among other points, that damage caused by harvesting operations can be minimized with adequate planning of harvesting operations, increased training of personnel for teamwork, and in general by adopting reduced impact harvesting techniques.